SETTLER AGGRESSIONS: INDIGENOUS DOCTORAL STUDENT EXPERIENCES WITH SETTLER COLONIALISM IN HIGHER EDUCATION - Allen, Emma Lea (University of Oklahoma – Graduate College, 2025)
Indigenous students pursuing doctoral education often navigate environments shaped by the historical and on-going settler colonial structure of the United States. This study aimed to examine the lived experiences of Indigenous doctoral students with microaggressions at Non-Native Colleges and Universities (NNCUs), with attention to how these incidents are shaped by underlying settler colonial dynamics. Using an Indigenous methodological approach, with Settler Colonialism and TribalCrit as guiding frameworks, data were collected through in-depth interviews with 11 Indigenous doctoral students from both public and private universities. The term “settler aggression” emerged in this study as a way to describe microaggressions rooted in settler colonialism and directed at Indigenous individuals or communities. The findings uncovered four themes of settler aggressions: Settler Ignorance, which is categorized as a structural lack of awareness that benefits the setter; Settler Tokenization (and Indigenous Labor), which illustrates how settlers utilize Indigenous people, knowledge, culture, or spirituality to appear diverse without bringing about real change; Environmental Settler Aggressions in the Academy, which are the systemic settler aggressions embedding within academic structures; and Settler as Supreme Sovereign, which reflects how settlers assert their dominance through the centering of their own authority, knowledge, and culture while marginalizing Indigenous people. This research highlights the need for higher education institutions to move beyond symbolic gestures and implement actionable policies that support, protect, and empower Indigenous students.
Keywords: Higher education; Doctoral education; Indigenous doctoral students; Microaggressions; Native students; settler aggressions